Operational and environmental evaluation of traffic movement on urban streets using GPS floating-car data - Elkafoury, Ahmed; Negm, Abdelazim; Hafez, Mohamed; Bady, Mahmoud; Ichimurac, Teijiro (International Journal of Engineering and Technology, 2014)
Evaluating traffic networks is vital for the management of traffic systems. Nowadays, Global Positioning System (GPS) technology, by independent GPS devices or GPS enabled cellular phones, is properly used in most vehicles, especially on urban streets, due to its cost effectiveness, ease of use, and real-time services. With its ability to detect the time position of the floating car, GPS devices introduces a new prospective to gather vehicle information. Collected information can be utilized for traffic management and for Intelligent Transportation System (ITS) to deduce evaluation indicators, and to achieve suitable measures. This paper brings up a framework for using real-time data collected by GPS-floating car technique for evaluating traffic conditions on urban streets. It utilizes GPS data of time, longitude, latitude to estimate evaluation indicators of street segments. This incorporates operational evaluation of street segment by characterizing Level of Service and level of congestion, and incorporates environmental evaluation by estimating the road-side concentration of pollutants emitted by traffic. Framework formation has been described. Different models used within every step of the framework have been investigated. Including models used in GPS data sample analysis, through models used to identify of street segments, and finally models used for street segments evaluation.